Wettability of substrata controls cell–substrate and cell–cell adhesions - Tzoneva, R.; Faucheux, N.; Groth, T. (Biochimica et biophysica acta, 2007)
The maintenance of endothelial cell (EC) monolayer architecture requires stable adhesions not only between neighboring cells but also between cells and the extracellular matrix. While the influence of biomaterials surface wettability on cell–substratum adhesion is rather well studied, its impact on cell–cell cohesion has not been extensively investigated. In the present study a model system consisting of hydrophilic and hydrophobic glass pre-coated with fibronectin and fibrinogen was used to study the influence of surface wettability on both types of cell adhesions. It was demonstrated that the substrate wettability controls the adhesion and cytoskeletal organization of endothelial cells, which has an impact on the subsequent ability of cells to establish stable cell–cell cohesions. These effects were related to the accessibility of specific domains of the adsorbed proteins. While the hydrophobic substratum promoted cell–cell cohesion, on hydrophilic substrata cell–substrate adhesion was dominant. In addition, evidence for an influence of surface wettability on the cross talk between integrins and cadherins was found.